The study of glass from the eastern Mediterranean, south Caucasus and east Africa in the late 8th–14th centuries AD: an interdisciplinary approach - Siu, Ieong (2017)
This study aims to increase our understanding of middle Byzantine, early Islamic, medieval Georgian and east African glasses in the late 8th – 14th centuries AD using typological, archaeological and scientific approaches.